Looking Beyond Government-Led Delivery of Water Supply and Sanitation Services : The Market Choices and Practices of Haiti’s Most Vulnerable People - World Bank (Washington, DC, 2017)
The Haiti water supply, sanitation, and hygiene (WASH) Poverty Diagnostic seeks to inform how to maximize the socioeconomic impact of the scarce fiscal resources channeled to the sector. The study assesses the linkages between improved access to WASH services, poverty, and health outcomes. The diagnostic also provides convincing evidence of the linkages between improved access to WASH services and variables affecting the adequate development of children in Haiti, with a particular focus on stunting. The diagnostic also analyzes the functioning of the water supply and sanitation (WSS) markets to identify ways to ensure that services delivered by the private sector are of good quality and affordable. Focusing on the metropolitan area of Port-au-Prince the diagnostic sheds light on the functioning of its water supply and fecal waste collection, transportation, and treatment services’ markets. Port-au-Prince has the largest and most sophisticated WSS market in Haiti, although not the fastest growing. Therefore, understanding how this market functions may aid stakeholders in addressing issues and opportunities that arise in other urban markets in the future, and in structuring successful public-private partnerships to serve rural communities.